Implementing a Midline Catheter Program in an Acute Care Hospital: Process and Outcomes. Issue 5 (September 2021) - Keleekai-Brapoh, Nowai; Fernandes, Nicole; Richards, Ann; Gilpin, Cornelia
Abstract : Midline catheters are a viable alternative to central vascular access devices in appropriate patients. Successful midline catheter programs require robust surveillance plans to monitor for appropriateness of use and complications, including bloodstream infections. This retrospective study evaluated the impact of implementing a midline catheter program in a midsize teaching medical center in the northeastern United States from January 2014 to May 2019. After implementation, the midline catheter utilization rate was 5.6% with bloodstream infections and other complication rates of 0.44 and 6.57 per 1000 midline catheter days, respectively. Results further revealed a reduction in central vascular access device utilization from 17.8% to 14.5% ( P < .001).